Pemanfaatan Limbah Tailing PT Indonesia Chemical Alumina Sebagai Bahan Campuran Batu Bata untuk Alternatif Pengurangan Limbah Industri Bauksit - Faizah Isyiqah; Wahyu Prayitno; Rizky Putranto (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This study evaluated the utilization of bauxite tailings from PT Indonesia Chemical Alumina as a mixture material for brick manufacturing to reduce industrial waste. A quantitative experimental method was applied using tailing compositions of 0%, 20%, 40%, and 80%. Bricks were produced through drying, sieving, mixing, molding, drying, and traditional firing according to SNI 15-2094-2000. The 20% tailing composition produced the highest compressive strength of 4.828 MPa, while the 80% composition showed the lowest value of 1.839 MPa. Water absorption increased with higher tailing content, ranging from 29.01% to 43.76%. The utilized tailing volume reached 0.003892 m³ at laboratory scale. The results indicate that bauxite tailings can be used as a brick mixture material and have potential for reducing industrial waste, although optimization is still needed to improve water absorption performance.